(untitled) (Issues in Social and Environmental Accounting (ISEA), 2013)
This paper reviews Climate Change, Justice and Sustainability, a symposium volume that examines how climate change and sustainability challenges disproportionately affect the world’s poor. The review evaluates the book’s central assumption that poverty constitutes multidimensional vulnerability—geographical, individual, and political—and is therefore essential to discussions of sustainable development. It highlights how the book’s authors frame poverty through varying manifestations such as water poverty, fuel poverty, and rights poverty, and how these forms of vulnerability interact with climate-related risks. The review also analyzes the book’s presentation of sustainability solutions, emphasizing compromises in climate mitigation and adaptation policies resulting from incomplete scientific knowledge, political bargaining, and economic trade-offs. Mitigation chapters reveal the tension between global warming targets and national economic interests, while adaptation chapters illustrate pathways for enhancing resilience in water management, agriculture, ecosystems, and marginalized forest-dependent communities. Overall, the paper concludes that poverty alleviation must be central to sustainability initiatives, as the poor contribute least to climate change yet bear its greatest burdens. The review positions the book as a valuable resource for researchers, educators, and practitioners by showcasing diverse country case studies and offering insights into the political, ethical, and operational dimensions of sustainable development